Cholesterol and Triglyceride Concentrations, COVID-19 Severity, and Mortality: A Systematic Review and Meta-Analysis With Meta-Regression - Angelo Zinellu; Panagiotis Paliogiannis; Panagiotis Paliogiannis; Alessandro G. Fois; Paolo Solidoro; Paolo Solidoro; Ciriaco Carru; Ciriaco Carru; Arduino A. Mangoni; Arduino A. Mangoni (Frontiers Media S.A., 2021)
Lipid profile alterations have been observed in patients with coronavirus disease 2019 (COVID-19) in relation to disease severity and mortality. We conducted a systematic review and meta-analysis with meta-regression of studies reporting total, HDL, and LDL-cholesterol, and triglyceride concentrations in hospitalized patients with COVID-19. We searched PubMed, Web of Science and Scopus, between January 2020 and January 2021, for studies describing lipid concentrations, COVID-19 severity, and survival status (PROSPERO registration number: CRD42021253401). Twenty-two studies in 10,122 COVID-19 patients were included in the meta-analysis. Pooled results showed that hospitalized patients with severe disease or non-survivor status had significantly lower total cholesterol (standardized mean difference, SMD = −0.29, 95% CI −0.41 to −0.16, p < 0.001), LDL-cholesterol (SMD = −0.30, 95% CI −0.41 to −0.18, p < 0.001), and HDL-cholesterol (SMD = −0.44, 95% CI −0.62 to −0.26, p < 0.001), but not triglyceride (SMD = 0.04, 95% CI −0.10 to −0.19, p = 0.57), concentrations compared to patients with milder disease or survivor status during follow up. Between-study heterogeneity was large-to-extreme. In sensitivity analysis, the effect size of different lipid fractions was not affected when each study was in turn removed. The Begg's and Egger's t-tests did not show evidence of publication bias, except for studies investigating LDL-cholesterol. In meta-regression, significant associations were observed between the SMD of LDL-cholesterol and age and hypertension, and between the SMD of triglycerides and study endpoint and aspartate aminotransferase. In our systematic review and meta-analysis, lower total, HDL, and LDL-cholesterol, but not triglyceride, concentrations were significantly associated with COVID-19 severity and mortality. Cholesterol concentrations might be useful, in combination with other clinical and demographic variables, for risk stratification and monitoring in this group.Systematic Review Registration: PROSPERO registration number: CRD42021253401.